Comparative Analysis of Cerebral Magnetic Resonance Imaging Changes in Nontreated Infantile, Juvenile and Adult Patients with Niemann-Pick Disease Type C - Gburek-Augustat, Janina; Groeschel, Samuel; Kern, Jan; Beck-Woedl, Stefanie; Just, Jennifer; Harzer, Klaus; Stampfer, Miriam; Kraegeloh-Mann, Ingeborg (Neuropediatrics, 2020)
Aim The study aims to describe cerebral MRI in different onset forms of Niemann-Pick type C (NPC). Systematic MRI analyses in this rare lysosomal storage disease are lacking in the infantile and juvenile onset forms.Methods Thirty-two cerebral MRI scans from 19 patients with NPC were assessed using a newly established and validated scoring system which addresses white matter changes and supratentorial versus infratentorial atrophy.Results Seven scans were from six NPC patients with early infantile onset (<2 years of age), six scans were from three patients with late infantile onset (2–6 years), six scans from four with juvenile onset (6–15 years), and 13 from six with adult onset (>15 years). While supratentorial atrophy was the leading sign in the infantile groups, the juvenile and adult forms were characterized by both, infra- and supratentorial atrophy. White matter changes were found in nearly every patient; they increased with the disease duration in the earlier forms and were prominent in the later forms already early in the disease course.Conclusion This is the first systematic and comparative MRI analysis in the different onset groups of NPC using a scoring system. Early during disease course, MRI showed different patterns in infantile compared with juvenile and adult onset NPC patients, for example, only supratentorial atrophy in juvenile versus global atrophy in adult onset patients. MRI changes provide an additional, early biomarker for NPC.
Keywords: Niemann-Pick type C; biomarker; MRI